The Development of Video Tutorials to Improve Computer Assembling Skills for Grade X TKJ SMK Students: Development of Video Tutorials to Improve Computer Assembling Skills for Grade X TKJ SMK Students - Yanti, Nur Eva; Hamdi Daming (CV. LAJAGOE PUSTAKA, 2023)
This study aims to determine the feasibility of video tutorials developed in terms of media aspects and content aspects to improve computer assembly skills for class X TKJ SMK students. This research and development refers to the ADDIE development model which consists of 5 stages, namely: analysis, design, development, implementation, and evaluation. The testing in this product consists of alpha test, beta test, and effectiveness test. The alpha test involved 2 material experts and 2 media experts to determine the feasibility level of the video tutorial product. The video tutorials produced proved to be very suitable for use to increase students' knowledge of assembling computers based on the assessment of material aspects 4.70 (very feasible), media aspects 4.09 (decent), small group responses namely teachers 4.27 (very feasible) and students 4.23 (very feasible), and the large group response 4.11 (decent)..